Entry market choices and post-entry growth patterns among born globals in consumer goods sectors. Issue 6 (12th November 2018) - Jin, Byoungho; Chung, Jae-Eun; Yang, Heesoon; Jeong, So Won
Abstract : Purpose: Contrary to the mainstream born global (BG) perspective, some previous studies report the incremental expansion of BGs. In addition, the reasons behind BGs initiating specific steps, if any, and BGs' entry market choices are still unknown or rather contrasting. This study views that such contrasting findings may be attributed to the contexts in which BGs operate. Within the context of consumer goods BGs, the purpose of this paper is to examine the entry market choices and post-entry growth patterns, and investigate the underlying reasons. Design/methodology/approach: This study adopted in-depth historiographic case research from seven Korean BGs in the consumer goods sector that demonstrated success in internationalization. Multiple sources were used to gather data from each case. A total of 14 interviews, approximately two one-on-one interviews per firm, were the major means of data collection. Findings: The findings revealed that first entry market choices among BGs functioned largely as attempts at emergent opportunities. However, after the first wave of entry into countries with available selling opportunities, entry market choice became a simultaneous pursuit of strategic markets and emergent selling opportunities. BGs focusing on image-oriented consumer goods appeared more strategic when entering the world's leading markets to gain brand reputation. The analyses of internationalization processes revealed three patterns, which collectively implied that each move to the next stage came from a strategic decision to solve the problems related to survival and strategic visions for growth. Originality/value: One contribution of this paper is the provision of empirical evidence for entry market choices among consumer goods BGs. The findings suggest that BGs' entry market choices may not be a simple matter of simultaneous expansion to the world's lead market. Instead, they may comprise more strategic decision. While previous studies have suggested such evolutionary or path-dependent internationalization processes, this study is among the first to reveal specific growth patterns and the possible reasons behind them.